2018
DOI: 10.4103/ijem.ijem_550_17
|View full text |Cite
|
Sign up to set email alerts
|

Premarriage counseling in Type 1 diabetes

Abstract: Type 1 diabetes is a challenging illness and needs lifelong diabetes self-care. At the same time, there is a significant stigma associated with it, especially with relation to marriage. There are concerns related to premarriage disclosure, marital relationship, ability to procreate, risk during pregnancy in women, and the risk of disease in children. In this document, we discuss the issue of disease-related stigma which may become a significant challenge for a prospective spouse and the impact of type 1 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…To our knowledge and consistent with the present study, no relationship has been established between marital union and the onset of type 1 diabetes among the male and female adults. However, adult-onset type 1 diabetes is purported to impact negatively on the social, psychological, and medicals aspects of marital union as reviewed recently by Priya and colleagues [21,22], adding more distress to the disease burden. In contrast, a recent population-based study documented in Brazil reported a significant association between marital union and diabetes mellitus among the general diabetes subjects [23].…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…To our knowledge and consistent with the present study, no relationship has been established between marital union and the onset of type 1 diabetes among the male and female adults. However, adult-onset type 1 diabetes is purported to impact negatively on the social, psychological, and medicals aspects of marital union as reviewed recently by Priya and colleagues [21,22], adding more distress to the disease burden. In contrast, a recent population-based study documented in Brazil reported a significant association between marital union and diabetes mellitus among the general diabetes subjects [23].…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…The topic of marriage is often neglected in diabetes management, and marital counseling is typically not offered by most diabetes clinics. Given that marriage quality is often associated with diabetes-related outcomes, offering premarital and marital counseling can be a critical component of long-term diabetic outcomes (Priya et al, 2018). Among couples dealing with chronic illness, those with divergent communication styles are more likely to report conflict and distress about the illness and their overall relationship (Rolland, 1994).…”
Section: Interpersonal and Cultural Considerationsmentioning
confidence: 99%
“…Optimal glycemic and metabolic control at this time is not only important to reduce the risk of severe COVID-19 infection, it also ensures optimal metabolic control. [ 58 ] This can be planned through scheduled telemedicine or physical visits, as necessary. [ 4 14 ] Additionally, periodic screening to assess any complications or comorbidities is strongly recommended.…”
Section: Pre-pregnancy Planning In Women With Pre-existing Diabetes D...mentioning
confidence: 99%
“…[ 4 14 ] Additionally, periodic screening to assess any complications or comorbidities is strongly recommended. [ 58 ] Folic acid supplementation should also be started. [ 3 4 ]…”
Section: Pre-pregnancy Planning In Women With Pre-existing Diabetes D...mentioning
confidence: 99%